"An Offer Not to Be Refused": Ideology and Communist Party Membership before 1968 in the Narratives of the Czechoslovak Officer Corps - Jiří Hlaváček (Wrocławski Rocznik Historii Mówionej, 2019)
This study focuses on the reflection of the relationship between the army and ideology in Czechoslovakia in the 1960s. The main attention is paid to the issue of membership of Czechoslovak People's Army officers in the Communist Party of Czechoslovakia before 1968. Through the analysis of oral-historical interviews, the author follows the narrative and legitimizing strategies of rejecting or accepting party membership, which was one of the conditions of career growth in the military during the period under review. An important factor in (re) constructing narrators’ memories in this case is the current media image of the communist regime in Czech society.